Mechanism of negative modulation of FSH signaling by salt-inducible kinases in rat granulosa cells - Armouti, Marah; Rodriguez-Esquivel, Miriam; Stocco, Carlos (Frontiers in Endocrinology, 2022)
The optimal development of preovulatory follicles needs follicle-stimulating hormone (FSH). Recent findings revealed that salt-inducible kinases (SIKs) inhibit FSH actions in humans and rodents. This report seeks to increase our understanding of the molecular mechanisms controlled by SIKs that participate in the inhibition of FSH actions in primary rat granulosa cells (GCs). The results showed that FSH causes a transient induction of Sik1 mRNA. In contrast, SIK inhibition had no effects on FSH receptor expression. Next, we determined whether SIK inhibition enhances the effect of several sequential direct activators of the FSH signaling pathway. The findings revealed that SIK inhibition stimulates the induction of steroidogenic genes by forskolin, cAMP, protein kinase A (PKA), and cAMP-response element-binding protein (CREB). Strikingly, FSH stimulation of CREB and AKT phosphorylation was not affected by SIK inhibition. Therefore, we analyzed the expression and activation of putative CREB cofactors and demonstrated that GCs express CREB-regulated transcriptional coactivators (CRTC2) and that FSH treatment and SIK inhibition increase the nuclear expression of this factor. We concluded that SIKs target the FSH pathway by affecting factors located between cAMP/PKA and CREB and propose that SIKs control the activity of CRTC2 in ovarian GCs. The findings demonstrate for the first time that SIKs blunt the response of GCs to FSH, cAMP, PKA, and CREB, providing further evidence for a crucial role for SIKs in regulating ovarian function and female fertility.